Etiological Factors and Clinical Patterns of Subfertility among the Couples Attending in a Tertiary Care Hospital in Bangladesh (Sir Salimullah Medical College Journal, 2022)
Subfertility, a global health issue is defined as the failure in pregnancy after one year of unprotected intercourse. It affects approximately 10%-15% of the couple in developed country1. It is not merely a health problem but also a matter causing social instability, marital disharmony and many disgraceful conditions. Regarding causes of subfertility, female factor, male factor, combined male and female factors and sometimes unexplained factors are responsible.Objective: The aim of the study was to find out the etiological factors and the patterns of subfertility among the couples attending the infertility clinic and outpatient department (OPD) of Kurmitola General Hospital of Bangladesh.Methods : This cross-sectional study was done at the OPD and infertility clinic of Kurmitola General Hospital during the period of January 2019 to- December 2019. Total 140 couples with necessary investigations were interviewed by structured questionnaire. Data analysis done under SPSS method.Result : In this study total number of 140 couples were studied. The frequency of primary and secondary subfertility was 55% and 45% respectively. Among 140 couples mean age of female was 32.6 year and mean age of male was 36.4 year. The mean duration of the subfertility among the couples was 7 year. Concerning the contribution of male and female factor among 140 couples, female factor was responsible in 55% case and male factor was responsible in 20% cases, 10% had combined male and female factor and in 15% couple causes of subfertility was unexplained. Regarding the etiology of subfertility among women, different factors included. Polycystic ovarian syndrome (PCOS) 46.15%, tubal factor 31.86%, endometriosis 8.79%, among hormonal disorder hypothyroidism was responsible in 5.49% and hyperprolactinemia in 2.19 % cases, and ovarian cause like poor ovarian reserve was responsible in 4.39% cases and uterine factor was responsible in 1.09% cases. To detect the male factors of subfertility semen analysis report was done., among male partner 69.04% had oligospermia, 16.66% show asthenospermia, another 9.52% show teratospermia. Azoospermia was detected in 4.76% cases.Conclusion: Bangladesh is a developing country where population burden is a big concern. On the other hand, reproduction is a basic human right. As the subfertility leads to physical, psychological and social problems so government needs to take care of this subfertility issue. This study gives us the idea of the needs and further demands of the services in our country to identify social cultural and economic factors associated with subfertility and interventions needed to overcome the current situation.Sir Salimullah Med Coll J 2021; 29(2): 136-140